Campanhas presidenciais na América Latina: convergências e divergências no discurso midiático - Saisi, Katia (2011)
This work aimed at discussing the relations between communication and politics in the current context of Latin America. For such purpose, we investigated the meanings movement of messages from and about the candidates to the Presidency of the Republic in three Latin American countries: Brazil (2010), Venezuela (2006), and Chile (2009/2010). Based on the television propaganda material and on the journalistic cover of the main printed vehicles in those countries, we tried to check the role of communication media as political discourse mediators, as well as the recurring political myths in presidential campaigns. To account for the complex Latin American realities, the adopted perspective was the comparative one, in order to understand both the internal heterogeneity and is external homogeneity. The results suggest both convergences and divergences, indicating a scenario in transformation, in which popular participation is placed as a growing value